Extended factors for the Theory of Planned Behavior in Chinese organic food consumption research—a systematic literature review on motives and barriers - Chen, Yihan; Othman, Rosly; Chong, Ye (Frontiers in Sustainable Food Systems, 2025)
In recent decades, global interest in organically produced food has expanded substantially; however, the understanding of the motives and barriers underlying its consumption remains incomplete, prompting increased scholarly attention to this topic. However, in the context of the Chinese market, there is a particular scarcity of research that, within the Theory of Planned Behavior (TPB) model, systematically analyzes newly introduced variables and determines whether they function as motives or barriers to organic food consumption. To address this gap, the present study systematically reviews 14 empirical articles on organic food consumption in China published between 2014 and 2024, and classifies and summarizes the relevant motives and barriers based on the consumption values theory and the innovation resistance theory. The findings indicate that the most frequently examined drivers include the conditional value of trust (n = 5), followed by health consciousness (n = 4) and revealed information (n = 2). Within the domain of social value, environmental concern (n = 3) emerges as a significant influence on Chinese consumers. Regarding barriers, an aspect less frequently analyzed in the reviewed literature, the present study identifies that existing studies primarily focus on value barriers, with price sensitivity and pricing policy. The findings aim to provide a more comprehensive, context-specific reference for advancing theoretical development and guide practical applications in this domain.